Karakteristik Belajar Anak Usia TPQ dan Adaptasi Metode Pengajaran Guru: Studi Kasus di TPQ Al-Muntaha Ali - Yokha Latief Ramadhan; Fatimah Deswina Azzahra (Hijaz: Jurnal Ilmu-Ilmu Keislaman, 2025)
This study aims to describe the learning characteristics of children at TPQ Al-Muntaha Ali and examine their implications for teachers’ instructional methods. The research employed a qualitative descriptive approach using observation, interviews, and documentation involving teachers and children aged 5–10 years. The findings indicate that children demonstrate varying levels of attention, motivation, learning pace, and participation during Qur’anic learning activities. To address these differences, teachers implement the Ummi method, provide rewards, and utilize interactive learning activities such as Islamic songs and group memorization. These strategies help maintain students’ engagement, improve learning motivation, and encourage social interaction among learners. The study concludes that understanding children’s learning characteristics is essential for designing effective and enjoyable learning environments in TPQ settings. The findings also imply that teachers need to adopt flexible and child-centered instructional approaches to optimize learning outcomes in nonformal Islamic education.